Dynamic analysis of train?bridge system subjected to non-uniform seismic excitations. - Xia, He
Based on the theory of dynamic wheel?rail interactions, a dynamic model of coupled train?bridge system subjected to earthquakes is established, in which the non-uniform characteristics of the seismic wave input from different foundations are considered. The bridge model is based on the modal comprehension analysis technique. Each vehicle is modelled with 31 degrees of freedom. The seismic loads are imposed on the bridge by using the influence matrix and exerted on the vehicles through the dynamic wheel?rail interaction relationships. The normal wheel?rail interaction is tackled by using the Hertzian contact theory, and the tangent wheel?rail interaction by the Kalker linear theory and the Shen?Hedrick?Elkins theory. A computer code is developed. A case study is performed to a continuous bridge on the planned Beijing?Shanghai high-speed railway in China. Through input of typical seismic waves with different propagation velocities to the train?bridge system, the histories of the train running through the bridge are simulated and the dynamic responses of the bridge and the vehicles are calculated. The influences of train speed and seismic wave propagation velocity on the dynamic responses of the bridge?vehicle system are studied. The critical train speeds are proposed for running safety on high-speed railway bridges under earthquakes of various intensities.
Keywords: Bridge; Train; Earthquakes; Dynamic response; Running safety; Non-uniform seismic excitation